Social skills of students in early childhood schools (Isnad) and primary schools in distance education in the Kingdom of Saudi Arabia - Almalki, Amal Abdullah; Zagzoog, Tagreed; Madini, Manal Ibrahem (Journal of Educational and Psychological Sciences, 2022)
This study aims to reveal the social skills differences between the male students of early childhood schools and primary schools for first grade in the distance education programs. The study follows the comparative descriptive approach. The sample of the study consists of (182) students. And are randomly chosen from the two domains of learning in Jeddah City. The evaluation technique for social skills is applied to measure the performance of students in both schools. The results of the study show that there are significant statistical differences in the social skills of first, second and third grade learners at a significance level 5% for Students in early childhood schools with female teachers were the highest at the arithmetic mean values ​​in social skills (85%) while students in primary schools with male teachers have shown a lesser degree of social skills performance (76.6%). The researcher recommended more scientific experiments on the early stages of children’s learning to highlight the effectiveness of the Early Childhood Program offered by the Ministry of Education in the Saudi Kingdom. It also recommends conducting similar studies that apply a unified database approach on other regions of Saudi Arabia.